The Relationship Between Institutions and Business Opportunities Toward Economic Growth - P Eko Prasetyo; Andryan Setyadharma; Nurjannah Rahayu Kistanti (Economics Development Analysis Journal, 2019)
This study aimed at explaining the relationship, and effects of human capital, entrepreneurial business opportunities, institutional economics, and regional economic growth. It was carried out to develop fundamental microeconomic model in rural development to assist human capital roles and institutions as well as entrepreneurial business for the economic growth. Further, the researchers used simultaneous system method in form of a recursive correlational path analysis model. This modeling system provides simplicity and easy understanding. The main source of the data were the empirical micro fundamental data of the business doers in rural areas measured by Gini index ratio. The findings showed that human capital and institutions were the main pillars in improving the quality of regional economic growth. Interestingly, there was a strong relationship between business opportunities and economic growth. However, the business opportunities had significantly negative effect toward the regional economic growth. These indicate the existence of a disturbance outside the model, namely the presence of bank credit which apparently made the business doers suffered losses. In this way, there is a need to examine further the reasons why the bank credits given to MSMEs negatively effect the economic growth.